2002
DOI: 10.1074/jbc.m202206200
|View full text |Cite
|
Sign up to set email alerts
|

In Saccharomyces cerevisiae, the Inositol Polyphosphate Kinase Activity of Kcs1p Is Required for Resistance to Salt Stress, Cell Wall Integrity, and Vacuolar Morphogenesis

Abstract: A problem for inositol signaling is to understand the significance of the kinases that convert inositol hexakisphosphate to diphosphoinositol polyphosphates. This kinase activity is catalyzed by Kcs1p in the yeast Saccharomyces cerevisiae. A kcs1⌬ yeast strain that was transformed with a specifically "kinase-dead" kcs1p mutant did not synthesize diphosphoinositol polyphosphates, and the cells contained a fragmented vacuolar compartment. Biogenesis of the yeast vacuole also required another functional domain in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
152
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 112 publications
(156 citation statements)
references
References 44 publications
4
152
0
Order By: Relevance
“…Snyder's group (4) thinks that there might be a hitherto unrecognized relationship between inositol pyrophosphates and PIKK-related processes, after they observed that yeast became immune to the toxic, growth-impeding effects of wortmannin and caffeine, if the IP 6 kinase gene, KCS1, was deleted. These results were a little surprising, because earlier reports contrarily indicated that kcs1⌬ cells were hypersensitive to both wortmannin (10) and caffeine (11). Nevertheless, Snyder's group was prompted by its observations to study the effects on telomere length when inositol pyrophosphate synthesis was targeted genetically.…”
Section: Regulation Of Telomere Lengthmentioning
confidence: 92%
“…Snyder's group (4) thinks that there might be a hitherto unrecognized relationship between inositol pyrophosphates and PIKK-related processes, after they observed that yeast became immune to the toxic, growth-impeding effects of wortmannin and caffeine, if the IP 6 kinase gene, KCS1, was deleted. These results were a little surprising, because earlier reports contrarily indicated that kcs1⌬ cells were hypersensitive to both wortmannin (10) and caffeine (11). Nevertheless, Snyder's group was prompted by its observations to study the effects on telomere length when inositol pyrophosphate synthesis was targeted genetically.…”
Section: Regulation Of Telomere Lengthmentioning
confidence: 92%
“…There are numerous ways how inositol pyrophosphates may regulate cell cycle progression, this may include events on vacuole biogenesis and cell wall integrity (Dubois et al, 2002), proper endocytic trafficking (Saiardi et al, 2002), cyclin-CDK-CDK inhibitor complex (Lee et al, 2007), chromatin remodelling (Steger et al, 2003) or RNA polymerase Imediated rRNA transcription (Thota et al, 2015) and for all of them understanding of structural analysis of diphosphoinositol polyphosphate kinase is crucial (Shears et al, 2013). Furthermore, above all of them, two might be of particular significance.…”
Section: Resultsmentioning
confidence: 99%
“…A major role of Ipk2 and its products, IP 4 and IP 5 , is transcriptional regulation by modulation of the chromatin remodelling in response to nutrients (Odom et al, 2000;Steger et al, 2003). The yeast Ipk1 and its product, IP 6 , which is generated by phosphorylation of IP 5 , regulate mRNA export through conjunction with Gle1 which regulates the activity of the DEAD-box protein Dbp5 at the nuclear pore complexes cytoplasmic face (York et al, 1999;Folkman et al, 2014) and nonhomologous end joining (Hanakahi et al, 2000). The synthesis of diphosphoinositol phosphates or pyrophosphates in yeasts is mediated by two kinases: Kcs1 phosphorylates IP 5 into 5-PP-IP 4 , and IP 6 into 5-PP-IP 5 (IP 7 ); Vip1 phosphorylates IP 6 into IP 7 isomer 1-PP-IP 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Cellular IP7 was measured as described previously (8,21). Details are found in SI Materials and Methods.…”
Section: Methodsmentioning
confidence: 99%
“…IP6K-deficient yeast manifest major abnormalities in vesicular endocytosis (8)(9)(10) and telomere length (11,12). Abundant evidence implicates PP-IPs in vesicular trafficking.…”
mentioning
confidence: 99%